Failure initiation and propagation characteristics of honeycomb sandwich composites - Othman, Abdul Rahim (2008)
he energy absorbed during the failure of a variety of structural shapes is influenced by material, geometry and the failure mode. Failure initiation and propagation of the honeycomb sandwich under loading involves not only non-linear behavior of the constituent materials, but also complex interactions between various failure mechanisms. Therefore, there is a need for an improved understanding of the material characteristics and energy absorption modes to facilitate the design of sandwich performance. In the present study, failure initiation and propagation characteristics of sandwich beams and panels subjected to quasi-static and impact loadings were investigated. Experimental studies involved a series of penetration and perforation tests on 2D beam and 3D panel configurations using a truncated cone impactor with impact velocities up to 10 m/s. Preliminary tests were also performed on the sandwich beams subjected to the three-point bending. Load-carrying, energy-absorbing characteristics and failure mechanisms under quasi-static and impact loading were determined. Dominant deformation modes involved upper skin compression failure in the vicinity of the indenter, core crushing and lower skin tensile failure.